Kalimat Efektif dalam Bahasa Indonesia untuk Sukses Berkomunikasi - Misnawati Misnawati; Yuliati Eka Asi; Anwarsani Anwarsani; Siti Muslimah; Ummi Ummi; Noor Lathifah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This article discusses effective sentences in Indonesian for successful communication, particularly in two common situations encountered in professional and educational environments. Case analyses involve examining real-life cases from various communication situations in daily life. These cases may include situations in both professional and educational settings. This analysis will assist researchers and readers in understanding the application of effective communication concepts in practical contexts, as well as reinforce understanding of the importance of effective sentences in communicating in the Indonesian language.